LAND TENURE DISPUTE BETWEEN KAPOK POGLAR RT 07 / RW 04 WEST JAKARTA CITIZENS AND METRO JAYA REGIONAL POLICE FROM THE PERSPECTIVE OF HUMAN RIGHTS - Felishella Earlene; Jesslyn Evelina Tandrajaya (Cepalo, 2019)
In Indonesia, frequently land disputes occurred between communities or the government with communities. Such as land disputes that arise between citizens of Kapuk Poglar RT 07 / RW 04 and Polda Metro Jaya. This research was combining using normative and empirical legal research methods. This research was conducted in  Kapuk Poglar RT 07 / RW 04. As for collecting and processing the data using qualitatively to understand the symptoms of the problem. This research aims to describe the relationship between this land disputes with citizens human rights and also the factors that cause land tenure disputes that occur in Kapuk Poglar RT 07 / RW 04 West Jakarta. The results of this research are known the factors that cause land tenure disputes that arise in Kapuk Poglar are overlapping, and there’s violence against human rights felt by Kapuk Poglar citizens in not obtaining the right to be free from fear and right to access water.